The Role of Public Figures amidst Indonesia’s Early Social Restrictions Policy on Twitter (X): A Social Network Analysis - Setiadi, Tatak; Pamuji, Eko (Information & Media, 2024)
The Government of Indonesia implemented large-scale social restrictions (Indonesian: Pembatasan Sosial Berskala Besar, abbreviated as PSBB) following the first confirmed cases of COVID-19. Due to social media role in information propagation, this decision quickly became a trending topic on Twitter. This study investigates the main actors and the dynamics of these discussions surrounding PSBB. Utilizing RStudio software, tweets containing the keyword „psbb“ and the hashtag #psbb were mined as of May 6, 2020. The data were analyzed and compared with research conducted during May 2020. Key findings include the significant role of the musician Fiersa Besari in shaping discussions about social restrictions, the emergence of seven major opinion leaders, and the prominence of online news outlets like detikcom and CNN Indonesia in the conversation. Additionally, the study highlights critical commentary from actors affiliated with the Democratic Faction of the Indonesian House of Representatives regarding the government‘s social restrictions policies. These findings provide insights into the network dynamics and public opinion on social restrictions during the early social restrictions policy in Indonesia.